Objectively measured adherence may affect side effects of mandibular advancement therapy in subjects with obstructive sleep apnea - Pahkala, Riitta (Sleep & breathing, 2024)
Purpose The purpose of this study was to determine if objectively measured adherence to oral appliance (OA) treatment may affect dental changes and temporomandibular disorders (TMD) in patients with obstructive sleep apnea (OSA). Methods The original study group consisted of adults with OSA who were referred for OA therapy. Eight indicators of subjective side effects of using OA (temporomandibular joint (TMJ) and muscle pain, pain in teeth, jaw stiffness in the morning, clicking, dry mouth, hypersalivation, gingival irritation) were evaluated by a questionnaire. Three occlusal indicators (overjet, overbite, molar occlusion) and clinical TMD signs (TMJ pain, muscle pain, clicking, jaw deviation on opening) were evaluated at baseline and at the 3-, 6-, and 12-month follow-up. In addition, objective adherence monitoring for OA was registered. Statistical analyses included the chi-square test, Fisher’s exact test, paired sample t -test, and linear regression analyses. Results A total of 58 adults with OSA were referred for OA therapy. Mean (SD) age was 50.7 (11.7) and mean apnea-hypopnea index (AHI) was 19.5 (10.0). At 1-year follow-up, the study group consisted of 28 men and 12 women. Overjet but not overbite reduced significantly after 1-year OA therapy. The average nightly wear of OA was related to overjet and overbite reduction, and to TMD signs. Hypersalivation, dry mouth, and tooth discomfort were the most common subjective side effects of OA therapy. Conclusion There was a time-dependent relationship with the nightly wear of OA and reduction in overjet and overbite, and clinical TMD signs. With 60% of mandibular advancement, dental changes and TM-disorders were considered mild/minor in the 1‐year study period.